ANALISIS STRUKTUR PERILAKU DAN KINERJA INDUSTRI MAKANAN ROTI DAN KUE DI KOTA PEKANBARU - Indriani, Sinaga; H, Ekwarso Hendro; Ufira, Isbah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to determine the market structure, conduct and performance of the bread and cake industry in Pekanbaru City. The population in this study were all bread and cake industries in Pekanbaru City with a total sample of 24 breads and cakes selected by the census method. The data used are secondary and primary data. Secondary data were sourced from the Pekanbaru City Industry and Trade Office and the Pekanbaru City Central Statistics Agency (BPS). Primary data were obtained from questionnaires. The data analysis method used is the Structure - Conduct - Performance approach theory. The variables used are market share, concentration ratio, Herfindahl Hirschman Index, capital labor ratio and price cost margin. The results of research on bread and cakes in Pekanbaru City had the highest market share of 13.715% while the lowest market share was 2.376%. The bread and cake industry in Pekanbaru City is a monopolistic market structure. The results of the analysis of the working capital ratio of the bread and cake industry in Pekanbaru City are capital intensive. The result of the performance of the bread and cake industry in Pekanbaru City is that profits are not influenced by market control. the results of the average PCM value of 8.416%.Keywords: Food industry, Market Share, IHH, CLR, PCM